Analisis Keunggulan Komparatif Dan Kompetitif Usaha Ternak Ayam Ras Pedaging Di Kecamatan Musuk Kabupaten Boyolali - Anisah Eka Mutmainah; Tinjung Mary Prihtanti (SEPA: Jurnal Sosial Ekonomi Pertanian dan Agribisnis, 2018)
This Research analyzed that comparative advantage and competitive of broiler chicken’s livestock business in Musuk Subdistrict of Boyolali Regency. For sampling uses a Saturated Sampling technique (census method) by taking all available samples as many thirty-two sample of broiler’s breeder around Musuk Subdistrict. To analyzed chicken livestock business uses Policy Analysis Matrik (PAM) and Ms. Excel as analysis tools. The result of this research shows that PCR (Private Cost Ratio) value  <1  is  0,63  that  means  the  commodity  system  of  broiler  chicken  which  is cultivated by breeder has a small competitive advantage. In addition to defraying domestic factor at private price, breeders are also able to compete with broiler chickens  livestock  business  in  other  region.  A  commodity  has  a  comparative advantage if it has DRCR (Domestic Resources Cost Ratio) value <1, the meaning is the profit obtained by the breeder is grater than the cost of social input non tradable. In case of broiler chickens in Musuk Subdistrict obtained grade DRCR <1 is 0,95 that means livestock business   produced has comparative competitiveness because it is able to finance domestic factors at social prices and is economically efficient.